2016
DOI: 10.1016/j.tins.2016.09.007
|View full text |Cite
|
Sign up to set email alerts
|

The Rise and Fall of the d -Serine-Mediated Gliotransmission Hypothesis

Abstract: D-Serine modulates NMDA receptors and regulates synaptic plasticity, neurodevelopment, and learning and memory. However, the primary site of D-serine synthesis and release remains controversial, with some arguing that it is a “gliotransmitter” and others defining it as a “neuronal co-transmitter”. Results from several laboratories using different strategies now show that the D-serine’s biosynthetic enzyme, serine racemase (SR), is expressed almost entirely by neurons, with few astrocytes appearing to contain D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
156
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 159 publications
(161 citation statements)
references
References 62 publications
4
156
1
Order By: Relevance
“…A knockout study of SR has clearly shown that mouse SR is expressed principally in soma of glutamatergic neurons and distributed in the olfactory bulb, cerebral cortex, basal ganglia (caudate-putamen), hippocampus, and substantia nigra (Miya et al., 2008). Expression of SR in astrocytes of mice had also been suggested in earlier studies (Panatier et al., 2006), but a conditional knockout study of SR in GFAP-positive astrocytes resulted in only minimal (≈10%) decrease in the hippocampus and no effects in the cortex or striatum (Benneyworth et al., 2012), suggesting that expression of SR in astrocytes is minor (cellular expression of SR is carefully discussed in other articles; Mothet et al., 2015; Wolosker et al., 2016). Contribution of astrocytes to D-serine-mediated NMDAR current is controversial since long-term potentiation at the hippocampal Schaffer collateral-CA1 synapse depends on astrocytic release of D-serine (Henneberger et al., 2010), whereas long-term potentiation at the Schaffer collateral-CA1 synapse is decreased by lack of neuronal but not astrocytic SR (Benneyworth et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A knockout study of SR has clearly shown that mouse SR is expressed principally in soma of glutamatergic neurons and distributed in the olfactory bulb, cerebral cortex, basal ganglia (caudate-putamen), hippocampus, and substantia nigra (Miya et al., 2008). Expression of SR in astrocytes of mice had also been suggested in earlier studies (Panatier et al., 2006), but a conditional knockout study of SR in GFAP-positive astrocytes resulted in only minimal (≈10%) decrease in the hippocampus and no effects in the cortex or striatum (Benneyworth et al., 2012), suggesting that expression of SR in astrocytes is minor (cellular expression of SR is carefully discussed in other articles; Mothet et al., 2015; Wolosker et al., 2016). Contribution of astrocytes to D-serine-mediated NMDAR current is controversial since long-term potentiation at the hippocampal Schaffer collateral-CA1 synapse depends on astrocytic release of D-serine (Henneberger et al., 2010), whereas long-term potentiation at the Schaffer collateral-CA1 synapse is decreased by lack of neuronal but not astrocytic SR (Benneyworth et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, recent studies indicate that only a small percentage of astrocytes express a negligible amount of SRR in rodent forebrain tissues (21). Pathological levels of d-serine, similarly to glutamate, have been implicated in mediating acute excito toxic cell death during pathological conditions (22)(23)(24)(25)(26); however, the effect of prolonged increases in d-serine levels on synaptic function remains to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…As we recently reviewed [1], studies from at least six laboratories now indicate that neurons rather than astrocytes are the major sources for D-serine and preferentially express its synthetic enzyme, serine racemase (SR), in the normal brain [1]. We described how several unforeseen artifacts misled established scientists (including ourselves) into believing that serine racemase and D-serine are localized exclusively to astrocytes and represent prima face exemplars of gliotransmission.…”
mentioning
confidence: 99%
“…We described how several unforeseen artifacts misled established scientists (including ourselves) into believing that serine racemase and D-serine are localized exclusively to astrocytes and represent prima face exemplars of gliotransmission. We were concerned that the purported astrocytic source of D-serine was being perpetuated to this day, despite compelling evidence to the contrary published over the past decade [1]. …”
mentioning
confidence: 99%
See 1 more Smart Citation